Review of photovoltaic and concentrated solar technologies including their performance, reliability, efficiency and storage - Moaz Osman; Imran Qureshi (Results in Engineering)
The transition to sustainable energy systems is increasingly driven by the development of solar technologies like Photovoltaic (PV) and Concentrated Solar Power (CSP) systems. This study provides a comprehensive comparison of these technologies, as well as analysing their performance, reliability, scalability, and efficiency across diverse applications and climates. PV systems, with efficiencies up to 30 %, excel in adaptability and scalability, making them suitable for residential, commercial, and large-scale deployments. CSP systems, capable of achieving efficiencies of up to 35 %, offer a unique advantage in providing dispatchable power through thermal energy storage, making them ideal for large-scale grid applications in high-irradiance regions. This research emphasises the complementary strengths of PV and CSP technologies in advancing global renewable energy goals. By integrating insights into technical performance, environmental impact, and economic feasibility, the findings highlight innovative strategies to enhance energy system reliability, efficiency, and sustainability, contributing to the ongoing energy transition.